The Conflict Of Interest About Gender Paradigm In West Sumatera - Reza Fahmi (Ar-Raniry: International Journal of Islamic Studies, 2015)
The Minangs are the world's largest matrilineal society; properties such as land and houses are inherited through female lineage. Some scholars argue that this might have caused the diaspora(Minangkabau, "merantau") of Minangkabau males throughout the Maritime Southeast Asia to become scholars or to seek fortune as merchants. However, the native Minangkabaus agreed that this matrilineal culture is indeed the result of (not the reason for) diaspora. With their men travelling out of the country for unspecified time (with possibility of some of them not returning home), it is only logical to hand the land and property to those who do not have to leave it: The women. This also ensures the women's (meaning: mothers of the future generations') welfare and hence ensuring their offsprings welfare. Besides, native MinangKabaus argue that "Men can live anywhere and hence they do not need a house like women do".